THE EFFECT OF ERGONOMIC EXERCISE ON URIC ACID LEVELS IN THE ELDERLY IN WUNUT VILLAGE, MOJOANYAR DISTRICT - Binarti Dwi Wahyuningsih (International Journal of Nursing and Midwifery Science (IJNMS), 2026)
THE EFFECT OF ERGONOMIC EXERCISE ON URIC ACID LEVELS IN THE ELDERLY IN WUNUT VILLAGE, MOJOANYAR DISTRICT MOJOKERTO REGENCY Binarti Dwi Wahyuningsih                                                                      UNIVERSITY Bina Sehat PPNI Mojokerto                                                                      binarti.dwiwahyuni@gmail.com   ABSTRACT Gout in the community cannot be ignored and requires numerous efforts, including lifestyle changes, developing education and knowledge about gout, and maximizing various methods to control uric acid levels to prevent complications. One preventative measure that can be taken to minimize the occurrence of hyperuricemia is exercise, such as ergonomic exercise. The purpose of this study was to determine the effect of ergonomic exercise on uric acid levels in residents experiencing elevated uric acid levels in Wunut Village, Mojoanyar District, Mojokerto Regency. The research method used was a single-group pre-test-post-test with the Wilcoxon test. The results of the study, which examined the p-value of uric acid levels in respondents after ergonomic exercises on days 1, 2, and 3, showed a p-value of 0.000 <α of 0.05. Ergonomic exercises can provide a heart massage due to the rise and fall of the diaphragm, opening blockages and improving blood flow to the heart and throughout the body. This facilitates the removal of uric acid residue.   Keywords: Gout, ergonomic exercises